2021
DOI: 10.3390/ijerph18126518
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Hospital Survey of Patient Safety Culture in Norwegian Hospitals: A Systematic Review

Abstract: This review aims to provide an overview of empirical studies using the HSOPSC in Norway and to develop recommendations for further research on patient safety culture. Oria, an online catalogue of scientific databases, was searched for patient safety culture in February 2021. In addition, three articles were identified via Google Scholar searches. Out of 113 retrieved articles, a total of 20 articles were included in our review. These were divided into three categories: seven perception studies, six interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 39 publications
4
20
1
5
Order By: Relevance
“…This could be attributed to the presence of management support for patient safety, the development of good communication between nurses and between nurses and their managers, as well as feedback about errors, nurses working as a team within hospital units, and continuous learning and improvement through attendance at training programs at both hospitals under study. This conclusion was consistent with and confirmed by Araújo et al (2022) [ 14 ], and Olsen & Leonardsen (2021) [ 21 ], who explained that the overall emphasis in quality and safety initiatives appears to be stressing features that change more at the unit level than at the hospital level. Furthermore, nurse leaders’ patient safety actions are related to how nurses evaluate their organizations and unit’s ability to provide safe patient care.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This could be attributed to the presence of management support for patient safety, the development of good communication between nurses and between nurses and their managers, as well as feedback about errors, nurses working as a team within hospital units, and continuous learning and improvement through attendance at training programs at both hospitals under study. This conclusion was consistent with and confirmed by Araújo et al (2022) [ 14 ], and Olsen & Leonardsen (2021) [ 21 ], who explained that the overall emphasis in quality and safety initiatives appears to be stressing features that change more at the unit level than at the hospital level. Furthermore, nurse leaders’ patient safety actions are related to how nurses evaluate their organizations and unit’s ability to provide safe patient care.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are congruent with those published by Alsabri et al (2022) [ 22 ] and Wu et al (2022) [ 23 ], who found that the examined healthcare organizations had a higher overall sense of patient safety culture. This finding, on the other hand, contrasted with Arajo et al (2022), and Olsen & Leonardsen (2021) [ 21 ], who discovered that the overall perception of patient safety had a moderate percentage and was considered an area for improvement due to hospital management, which values patient safety problems to a certain extent.…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, the new dimensions formed among the Hungarian sample (dimensions 2, 5, 11 and 12) had better reliability values than the dimensions formed by the original items. When comparing reliability with other EU countries, including Croatia (Brborović et al , 2014), Slovenia (Robida, 2013), Sweden (Nordin et al , 2013) and Norway (Olsen, 2008), lower Cronbach’s α values were also found in most dimensions (Table IV). Cultural differences between Europe and the USA should be considered when adapting the US HSOPSC as it is also indicated in the Croatian validation (Brborović et al , 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Another issue is the complexity of measures and the length of improvement programmes. Empirical research illustrates the difficulties of improving safety culture quickly, and that safety intervention could build on more refined theoretical models [39]. These issues should also be considered when developing OSH measures in organisations.…”
Section: Discussionmentioning
confidence: 99%